2013
DOI: 10.1021/ie402347g
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Chitosan and Titanium Dioxide on the Removal of Toxic Dyes by the Photodegradation Technique

Abstract: The photodegradation of three different types of dyes like an anionic dye, a cationic dye, and a zwitterionic dye, namely, Reactive Red 2 (RR), Methylene Blue (MB), and Rhodamine B (RB), respectively, have been carried out using chitosan/TiO 2 composite (CTC). The as-synthesized CTC was characterized by Fourier transform infrared (FTIR) spectral studies, scanning electron microscopy (SEM), energy dispersive analysis of X-ray (EDAX), BET, X-ray diffraction (XRD), and thermal analysis (thermogravimetric analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(51 citation statements)
references
References 37 publications
6
45
0
Order By: Relevance
“…Farzana and Meenakshi studied the photocatalytic degradation of MB using a chitosan–TiO 2 composite (CTC) and reported a MB (50 mg/L, 50 mL) degradation of over 93% for CTC (100 mg) in 60 min . The highest photocatalytic degradation is achieved with a 140 W light lamp . Current study showed over 98% degradation of MB (10 mg/L, 10 mL) for aerochtin–TiO 2 composite (10 mg) in 200 min.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Farzana and Meenakshi studied the photocatalytic degradation of MB using a chitosan–TiO 2 composite (CTC) and reported a MB (50 mg/L, 50 mL) degradation of over 93% for CTC (100 mg) in 60 min . The highest photocatalytic degradation is achieved with a 140 W light lamp . Current study showed over 98% degradation of MB (10 mg/L, 10 mL) for aerochtin–TiO 2 composite (10 mg) in 200 min.…”
Section: Resultsmentioning
confidence: 74%
“…6 mg/L, 50 mL) in 30 min for their material (100 mg) . Farzana and Meenakshi studied the photocatalytic degradation of MB using a chitosan–TiO 2 composite (CTC) and reported a MB (50 mg/L, 50 mL) degradation of over 93% for CTC (100 mg) in 60 min . The highest photocatalytic degradation is achieved with a 140 W light lamp .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Kobayakawa et al studied the complete mineralization of lignin using TiO 2 as photocatalyst. [20][21][22] Such synergetic effect was reported using powdered TiO 2 and activated carbon (AC) in the sorption and catalytic degradation of organic pollutants. 19 However, in recent years integrated adsorption and degradation are emerging as a more efficient and simplest technology for waste water treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The release of dye effluents from textile and photographic industries into water bodies are becoming a major source of water pollution due to complex aromatic molecular structure of dyes which makes them more stable, resistance to chemical, photochemical and biological degradation [1]. The anthraquinone dye has been applied widely in the printing and dyeing industries due to its bright color, high fixation and good color fastness [2].…”
Section: Introductionmentioning
confidence: 99%